SCIENTIFIC CONCEPTS AND THEORETICAL VIEWS ON THE CONCEPT OF “NORM MAKING” - Khujanazarov Azizjon Anvarovich (Modern American Journals, 2025)
This scientific article provides a comprehensive analysis of scientific concepts and theoretical views on the concept of "norm creation". At the same time, the author has developed definitions in order to form a unified approach to the concept of "norm creation".
Keywords: Law, norm, digitization, state, system, normative, expertise, institutional, legislation.